WOMEN SECURITY SAFETY SYSTEM USING ARTIFICIAL INTELLIGENCE (International Journal of Food and Nutritional Sciences, 2023)
Artificial intelligence is the ability of a system to understand and interpret external data through algorithms or machines or systems to solve problems. This AI term is used for knowledge based system, text mining, pattern recognition, language processing, natural language, decision making and knowledge based system etc.Today it is being used in environment, defense, technology and security. This article attempts to understand the opportunities and challenges of AI. It focuses on policies that are designed to ensure the development and deployment of AI-based systems.